2019
DOI: 10.1016/j.jid.2018.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Identity and Location within the Dermis Determine the Function of Papillary and Reticular Fibroblasts in Human Skin

Abstract: Human skin dermis is composed of the superficial papillary dermis and the reticular dermis in the lower layers, which can easily be distinguished histologically. In vitro analyses of fibroblasts from explant cultures from superficial and lower dermal layers suggest that human skin comprises at least two fibroblast lineages with distinct morphology, expression profiles, and functions. However, while for mouse skin cell surface markers have been identified, allowing the isolation of pure populations of one linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 47 publications
(76 reference statements)
9
145
0
4
Order By: Relevance
“…Recent work by Tabib et al already suggested a higher heterogeneity of dermal FBs than previously expected . Although our study revealed some similarities with their work, we found major differences between our and their analyses.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Recent work by Tabib et al already suggested a higher heterogeneity of dermal FBs than previously expected . Although our study revealed some similarities with their work, we found major differences between our and their analyses.…”
Section: Discussionsupporting
confidence: 52%
“…As FBs have been described to show phenotypic heterogeneity, gene expression, and ability to synthesize ECM, we next wanted to compare the transcriptomes of every identified FB cluster (Data will be made available upon request). Interestingly, this comparison did not reveal the classical discrimination of papillary and reticular FBs, since markers for these FB subsets, such as netrin 1 ( NTN1 ), podoplanin ( PDPN ), and matrix Gla protein ( MGP ), were detected in all FB clusters (Figure S5). We also screened our data set for genes which have recently been shown to identify major FB subsets in the skin, such as THY1 , FAP , secreted frizzled‐related protein 2 ( SFRP2 ), and flavin containing monooxygenase 1 ( FMO1 ) .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations